(untitled) (Research, Society and Development, 2022)
Introduction: Studies have described clinical characteristics of individuals with coronavirus disease (COVID-19). However, there are still few data on the clinical characteristics in the post-covid period. Objective: to describe the clinical and epidemiological characteristics of 267 individuals in the Amazon in the post-covid period. Methods: This is an observational epidemiological study, with a cross-sectional design, guided by the STROBE tool. Where we retrospectively interviewed adults who had laboratory-confirmed COVID-19 infection seen at the Primary Health Care (PHC) of the Municipality of Cachoeira do Piriá, during the COVID-19 pandemic from January to February 2021. Sociodemographic data, clinical history and care, comorbidities, and treatment were recorded for each of the 267 individuals over 18 years of age. Results: Females were predominant in 61.7% (n=165). Individuals reported as coexisting risk medical conditions, hypertension as the most common comorbidity in 14.6% (n=39). In this study, 57% (n=152) of people reported tiredness/fatigue as the main symptom that persisted for more than 3 months. Fever was the most reported first sign in 25.3% (n=67). Conclusions: There is a need for multidisciplinary follow-up to support PHC.